Institutional Ownership and Firm Value: Conditional Process Model (CPM) - P, Perwito; Zulbetti, Rita; Mubarok, Rifqi Ali; Setiawan, Ilham; Azyuranie, Rezqya. A (Dinasti Publisher, 2025)
The effect of institutional ownership on firm value with the conditional process model (CPM) approach: This study aims to test and analyze how and when Institutional Ownership is effective in increasing Firm Value. The research method uses a quantitative approach, the research design uses a descriptive approach, and an explanatory survey to test and analyze causal relationships. Research on public companies in Indonesia in the consumer-non-cyclical sector, as much as 488 pooled times series data with the analysis period 2016-2023, with the Conditional Process Model (CPM) approach to explain how (Mediation effect) and when / under what conditions (moderation effect) the effect occurs on the institutional ownership structure on firm value both directly and indirectly, to estimate the research model using Macro for SPSS V3.4. Research findings: institutional ownership, investment efficiency, and an independent board of commissioners affect increasing the value of the firm, The researcher produced a model formula that institutional ownership of the firm value through investment efficiency, is more visible to the company by involving an independent Board of Commissioners that leads to a high level, and investment efficiency can be used as a mitigation in making investment policies that can produce positive returns, increase the value of the company, so that it can compete sustainably.